Editorial: CHANGING DEVELOPMENT PATH OF QUAESTIONES GEOGRAPHICAE IN THE FIELD OF HUMAN GEOGRAPHY AND SPATIAL MANAGEMENT - Stryjakiewicz, Tadeusz (Quaestiones Geographicae, 2021)
This volume of Quaestiones Geographicae allows me to announce that this December marks the end of my 15-year run as Managing Editor of the journal in the field of Human Geography and Spatial Management. Established in 1974 as an annual of the then Institute of Geography of Adam Mickiewicz University in Poznań, Quaestiones Geographicae has undergone sever- al turns of fate in its 47-year history; in the dif- ficult times of the post-socialist transformation, the journal even had a break of several years in its activity.